The Effect of Organizational Culture on Employee Performance at PT. Maiwa Artha Promosindo Makassar - Fitriyani, Dwi Audiyah; Niswaty, Risma; Aslinda, Andi (Jurnal Administrasi Bisnis, 2026)
The cultural impact of the organization's performance on the employees' performance in maiwa artha promosindo makassar. Thesis the science administration study program. Majoring in administrative science. Faculty of social and law studies. Makassar state university. (Risma niswaty and Andi aslinda). The study aims to find out how the organizational culture affects the performance of employees in malwa artha promosindo makassar became the object of his research. It USES the kind of quantitative research. The data-gathering technique used is through primary data collection (observation and questionnaire) and secondary data collection (library study and documentation). The sample used was the sample that was calculated using sugiono's total sampling technique as many as 30 people surveyed. Data is obtained from research processed using data analysis and using the help of a 25 version of SPSS software program consisting of valiance tests and diagnostic tests of research instruments and descriptive analytic and inferential analysis of the data obtained. The results showed that the organizational culture and employee performance variables at PT. Maiwa Artha Promosindo Makassar has a significant influence. This was proven based on the results of a simple linear regression test and a correlation coefficient test of 0.675, which means that the relationship between organizational culture and employee performance is strong/high. The determinant coefficient obtained is 0.437 which means that the influence of organizational culture on employee performance at PT. Maiwa Artha Promosindo Makassar obtained a score of 43.7% which is included in the moderate category interval.